EFEK PENAMBAHAN BUBUK KENCUR (Kaempferia galanga) PADA PAKAN BUATAN TERHADAP PERTUMBUHAN IKAN GURAMI (Osphronemus goramy) - Zulkhasyni, Zulkhasyni; Sahary, Nilam; Ahmad, Nasir; Syukhriani, Silvy (University of Prof. Dr. Hazairin, SH, 2025)
This research aims to determine the effect of adding kencur powder (Kaempferia galanga) to artificial feed on the growth of gourami fish (Osphronemus goramy). This research was carried out in April – June 2024 in Bengkulu City for 60 days. The container uses Styrofoam measuring 50 cm x 30 cm x 30 cm. The test fish used were gourami seeds measuring 6 – 8 cm. This research used a Completely Randomized Design (CRD) with 4 treatments and 6 replications, so 24 research units were obtained consisting of P1 (without the addition of galangal powder), P2 (2 gram kencur powder), P3 (4 gram kencur powder) and P4 (2 gram kencur powder). kencur 6 grams).. The results of the research showed that the effect of adding kencur powder to feed had a highly significant effect on weight gain and length parameters, and had a significant effect on feed conversion but had no real effect on efficiency and survival. The best effect of adding galangal powder was the addition of 2 grams of kencur powder with a survival rate of up to 98%. For farmers to use 2 grams of kencur powder per 100 g of feed as a natural additive to support the growth of gourami, without reducing feed efficiency or survival.